Cissampelos keniensis (Menispermaceae), a new species from Mt. Kenya, East Africa - Zhou, Ya-Dong; Mbuni, Yuvenalis; Hu, Guang-Wan; Zhong, Zhi-Xiang; Yan, Xue; Mwachala, Geoffrey; Wang, Qing-Feng (Phytotaxa, 2017)
Cissampelos keniensis, a new species of Menispermaceae described and illustrated here, was collected from the rainforest on the eastern slope of Mt. Kenya. It is distinguished from all other tropical East African species in the genus by its cordate leaves, 4-locular synandrium, glabrous drupes and suborbicular-bilaterally compressed endocarp. A key to distinguish among the eight species of Cissampelos known from tropical East Africa is proposed.